2009
DOI: 10.1093/chemse/bjp048
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of New Analogs of the Sweet Protein Brazzein

Abstract: We have previously modeled the interaction of the sweet protein brazzein with the extracellular domains of the sweet taste receptor. Here, we describe the application of that model to the design of 12 new highly potent analogs of brazzein. Eight of the 12 analogs have higher sweetness potency than wild-type brazzein. Results are consistent with our brazzein-receptor interaction model. The model predicts binding of brazzein to the open form of T1R2 in the T1R2-T1R3 heterodimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…A brief review of previous studies reveals that majority of investigations have been conducted for determining of factors responsible for sweetening features of the protein [7][8][9][10][11][12][13]. Among them, more studies have been performed by means of site-directed mutagenesis to identify the key residues and regions of the protein which are important in the sweetening power of Brz [9,[14][15][16][17]. The majority of these investigations emphasized the importance of surfaced-exposed regions of protein and the proportion of its surficial charge to the whole length of protein.…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of previous studies reveals that majority of investigations have been conducted for determining of factors responsible for sweetening features of the protein [7][8][9][10][11][12][13]. Among them, more studies have been performed by means of site-directed mutagenesis to identify the key residues and regions of the protein which are important in the sweetening power of Brz [9,[14][15][16][17]. The majority of these investigations emphasized the importance of surfaced-exposed regions of protein and the proportion of its surficial charge to the whole length of protein.…”
Section: Introductionmentioning
confidence: 99%
“…Sweetness involves interactions that include the formation of hydrogen bonds and ionic bonds between sweet proteins and the sweet receptor. Modeling studies have suggested that the surfaces of sweet proteins interacting with the receptor are predominantly positive . Previously, we reported that mutants (His31Arg and His31Arg/Glu41Ala) that increased the positive charge and reduced the negative charge largely increased the sweetness .…”
Section: Resultsmentioning
confidence: 89%
“…Role of the β-sheet is less studied and disscussed. The direct mutagensis studies showed when the hydrophobic residues in the β-sheet are alanine substituted, biological function of mutated proteins are dromatically reduced (Walters et al, 2009;Yang et al, 2009). The maximal effects of mutated proteins are only 30-40% maximal effects of the wild type, even at a high protein concentration.…”
Section: Biological Distribution and Functionsmentioning
confidence: 99%
“…In both cases, similar positions along the structures are discovered that are crucial to functions of both peptides ( Figure 5). These sites are widely distributed on β1 strand, loop 1, loop 2 and loop 3 (Assadi-Porter et al, 2000;Walters et al, 2009;Yang et al, 2009). From the molecular docking models, these sites either directly interact with their targets or play as functional epitopes and insert into the active site of their targets (Assadi-Porter et al, 2010;Liu et al, 2006;Yang et al, 2009).…”
Section: Site-direct Mutagenesismentioning
confidence: 99%